Future 4 Teens: A Community-Based Therapeutic Model for African American Youth. Issue 3 (2nd July 2020) - Pritchett-Johnson, Brandi; Jones, Martinque K.
ABSTRACT: Culturally grounded therapeutic services orchestrated to meet the needs of African American youth remain sparse. The authors address this gap in the areas of scholarship and clinical practice by detailing Future 4 Teens (F4T), an integrated community therapy and education service model targeting African American youth ages 12– 21 years old. Based on interview data from former F4T participants ( n = 8; M age = 21.62 years), the authors also highlight salient components of the interventions contributing to its effectiveness and subsequent impact on African American youth's psychosocial functioning and academic engagement.